School Closure During COVID-19 Outbreak: Parental Attitudes and Their Experiences - Chuong, Hock Ting; Jeffery, Stephen; Ahmad Khairi, Hassan; Norashikin, Abdul Moris; Noor Nasuha, Noor Hamal; Nurul Ain, Amidar; Mohd Azlan, Rusdi (2021)
Introduction: COVID-19 brought closure to educational facilities. In this study, we want to explore how sociode-mographic factors affect parental attitudes and their experiences during the pandemic related to school closure. Ob-jectives: In this study, we are exploring the parental attitudes and their experiences during the school closure due to COVID-19 outbreak. Methodology: A cross-sectional survey was conducted in Malaysian households of 273 parents with children aged <18 years between May and June 2020 by distributing a structured online questionnaire. Socio-demographic, attitudes, and experiences variables were explored and analyzed using the chi-square test and Fisher exact test. We determined the association between sociodemographic factors (parent working status and school affiliation of children) with four attitudes of a parent (extent of school closure seen as a problem, plan for childcare, permit out-of-home activities and who cared for the child) and parental experiences (impacts on parental employ-ment - missed work, lost pay or income, the financial cost in excess during the pandemic comparing to typical days expenses and felt at risk of losing a job). Results: 97.4% of the respondents agreed with the school closure due to the severity of COVID-19. Having both parents working (61.9%), having a plan for childcare (88.64%), parents permit outdoor activities (21.24%) and availability of caretaker for the child (82.42%) were factors associated with “school affiliation of children”. It was found that 56.0% of parents who were working, had missed their works during the school closure. School affiliation was significantly associated with parental employment. Conclusion: This study had shown that the majority of the parents were significantly affected by the school closure together with their children due to COVID-19 pandemic in which they stayed at home for valid and essential reasons. The parents’ perspectives and attitudes toward the government’s policies on any pandemics should be studied in future.